A instrução secundária nas Alagoas: as aulas avulsas e o Liceu Provincial (1784-1892) - Santos, Ivanildo Gomes dos Santos (2018)
The purpose of this thesis is to reconstruct and reinterpret historically the constitution, organization and the process of structuring secondary education in Alagoas, notably the single classes and the Provincial High School of Alagoas. Located in the field of school institutions and cultures, among which are the subjects, in their dynamics of relations of power and interdependence, the temporal and architectural space and the school disciplines proving disseminated knowledge. The temporal delimitation, demarcated between 1784 and 1892, refers to the period between the locations, until then, of the first public secondary teacher of Alagoas, João Mendes Sanches Salgueiro, the reform Gabino Besouro, promulgated by State Decree nº 12, of December 9, 1892. The reform was the first major change in the teaching of the Lyceum de Alagoas, when the Establishment began to count on three types of teaching: the Course of Preparatories, the Normal Course and the Commercial Course, and for the first time they come to appear the so-called scientific subjects. The debate about school culture starts from the concepts developed by Chervel (1990), Julia (2001), Viñao Frago (1995) and Escolano (1992, 1993-94). The thesis is that every normative, disciplinary and didacticpedagogical apparatus in secondary education in Alagoas aimed at disciplining and adapting the behavior of a certain social group to assume the administrative and command posts in the Province. Therefore, its content was intentional, since it had as objective to inculcate certain knowledge and values, in order to guarantee to the elites the maintenance of its status quo. The thesis are based on the categories developed by the German sociologist Norbert Elias (1897-1990) and his conceptual framework on the civilizing processes, especially in the sense of understanding the internal and interdependent relations in the single classes and in the Lyceum. Elias studied the ramifications of interdependence built by individuals, and found that these connections give rise to social configurations: family, village, city, state, nations. To the concept of configuration it is also possible to insert the school institution, as a space that aggregates a group of human beings essentially interdependent and, therefore, imbricated in the tense relations of power. It was from this theoretical-methodological perspective that I analyzed the various sources, with which I compose the documentary corpus of the research, namely: newspaper articles and images, in addition to the official documents, such as: "statements" and presidents' reports of the Province and inspectors of public education, laws, regulations, ordinances, decrees, minutes, class maps, statistical data, budgets, lists of teachers.